Cystic presentation of primary hepatic neuroendocrine tumour: a case report with a brief review of literature - Mangesh Londhe; Sakshi Garg; Sushama Gurwale; Charusheela Gore (Open Exploration Publishing Inc., 2023)
Neuroendocrine tumours (NETs) are a rare type of tumours that arise from the neuroendocrine cells which are distributed throughout the body. Of all the gastrointestinal tumours only 1-2% account for NETs. They have an extremely low incidence of 0.17% arising in the intrahepatic bile duct epithelium. Majority of hepatic NETs occur as a result of metastases from the primary NETs. Most cases of primary hepatic NET (PHNET) present as a solid nodular mass. However, predominantly cystic PHNET is extremely rare which mimics other cystic space-occupying lesions clinically and radiologically as seen in this case.